Strong plasmon–exciton interactions on nanoantenna array–monolayer WS2 hybrid system - Liu, Lin (2020)
Strong plasmon–exciton interactions in monolayer transition-metal dichalcogenides (TMDs) is emerging as a promising material platform for light emissions, nonlinear optics, and quantum communications, and their realizations require highly localized electric fields parallel to the transition dipole moment of TMD excitons. Here, a systematic study of light–matter interaction in planar dimer nanoantenna of nanoscale gaps coupled with monolayer WS2 is presented, where the effects of the local field enhancement and spatial mode overlap in the plasmon–exciton coupling strength are experimentally investigated. Importantly, anticrossing behaviors in the strong coupling regime with a Rabi splitting of Ω = 118 meV for gold bowtie antennas with 7 nm gaps and Ω = 138 meV for gold dimer arrays with 10 nm gaps are demonstrated.